Histopathological Study of Gastroduodenal Biopsies and to See the Prevalence of Helicobacter Pylori with the Help of Special Stains in Selected Cases in North East India- A Cross Sectional Study in a Tertiary Care Centre - Sarma, Usha; Kalita, Upasana (Asian Pacific Journal of Cancer Biology, 2024)
Background: Acid peptic disease (APD), including gastric ulcers, duodenal ulcers, and gastro esophageal reflux disease is a common disorder of the gastrointestinal region, the pathogenesis of which involves an imbalance between acid secretion and gastric mucosal defenses. Acid peptic diseases mostly affect the esophagus, stomach, and duodenum. The imbalance could be caused by factors such as H pylori infection and acid secretory abnormalities in APD. Helicobacter pylori infection is a factor in 85% to 100% of duodenal ulcers and 70% to 90% of gastric ulcers. Besides, malignancies are also fairly common in these regions. Due to long standing APD or H. Pylori infection it may lead to dysplastic changes or malignancy in this region. These disorders are easily detected by endoscopy nowadays. This is a cross-sectional study done in 100 cases of gastroduodenal biopsies in a 1 year period. Aims and Objectives: To see the histopathological spectrum of gastroduodenal lesions and to detect the presence of H. pylori infection in suspected cases with the help of special stains in North East India. Result: There were 13 cases (%) of Helicobacter pylori gastritis diagnosed by H&E and Giemsa staining procedure. Out of the 13 cases, the highest number of cases, 46.1% was in the age group of 51-60 years. Out of the 13 cases of H. Pylori gastritis, 11 cases (84.6%) were male and 2 cases (15.3%) were female. The male: female ratio is 5.5 : 1.